Upper Respiratory Microbiome in Pregnant Women: Characterization and Influence of Parity - Giulia Solazzo; Simona Iodice; Jacopo Mariani; Nicola Persico; Valentina Bollati; Luca Ferrari (Microorganisms, 2022)
During pregnancy, the woman’s immune system changes to support fetal development. These immunological modifications can increase the risk of respiratory diseases. Because the respiratory microbiome is involved in airway homeostasis, it is important to investigate how it changes during pregnancy. Additionally, since parity is associated with immune system alterations and cohabitants shared a similar microbiome, we investigated whether having a child may influence the respiratory microbiome of pregnant women. We compared the microbiome of 55 pregnant with 26 non-pregnant women using 16S rRNA gene sequencing and analyzed taxonomy, diversity, and metabolic pathways to evaluate the differences among nulliparous, primiparous, and multiparous women. The microbiome was similar in pregnant and non-pregnant women, but pregnant women had higher alpha diversity (Chao1 p-value = 0.001; Fisher p-value = 0.005) and a lower abundance of several metabolic pathways. Multiparous pregnant women had a higher relative abundance of Moraxella (p-value = 0.003) and a lower abundance of Corynebacterium (p-value = 0.002) compared with primiparous women. Both multiparous (pregnant) and primiparous/multiparous (non-pregnant) women reported a higher abundance of Moraxella compared with primiparous (pregnant) or nulliparous ones (p-value = 0.001). In conclusion, we characterized for the first time the upper airway microbiome of pregnant women and observed the influence of parity on its composition.